2021
DOI: 10.1200/cci.20.00102
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning to Predict Tamoxifen Nonadherence Among US Commercially Insured Patients With Metastatic Breast Cancer

Abstract: PURPOSE Adherence to tamoxifen citrate among women diagnosed with metastatic breast cancer can improve survival and minimize recurrence. This study aimed to use real-world data and machine learning (ML) methods to classify tamoxifen nonadherence. METHODS A cohort of women diagnosed with metastatic breast cancer from 2012 to 2017 were identified from IBM MarketScan Commercial Claims and Encounters and Medicare claims databases. Patients with < 80% proportion of days coverage in the year following treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…The 5-year survival rate of patients with MBC is around 38% [2]. Notwithstanding, several studies [3][4][5][6] have shown that adherence to anticancer treatments is a critical issue in the disease trajectory of patients with breast cancer, especially regarding oral anticancer treatments (OATs), which are intensely demanding because patients are responsible for assuming medications according to the medical prescriptions, thereby increasing the risk of not appropriately taking the therapy [7].…”
Section: Adherence To Oral Anticancer Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5-year survival rate of patients with MBC is around 38% [2]. Notwithstanding, several studies [3][4][5][6] have shown that adherence to anticancer treatments is a critical issue in the disease trajectory of patients with breast cancer, especially regarding oral anticancer treatments (OATs), which are intensely demanding because patients are responsible for assuming medications according to the medical prescriptions, thereby increasing the risk of not appropriately taking the therapy [7].…”
Section: Adherence To Oral Anticancer Treatmentsmentioning
confidence: 99%
“…Accruing evidence have highlighted that patients with advanced cancer might report significant levels of nonadherence because in case of some cancers such as MBC, the patients have to change the type of treatments or dosage frequently and they experience a high level of fear of cancer spread [3]. For example, Yerrapragada and colleagues [6] reported nonadherence to tamoxifen in patients with MBC, ranging between 30% and 85% and further reducing over time. In addition, patients with MBC reported several barriers to the daily management of OAT, such as emotional (eg, worry, depression) and physical distress related to the side effects (eg, fatigue, weakness, sleep disturbance, emotional burden, pain) and lack of knowledge about their disease.…”
Section: Adherence To Oral Anticancer Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 ML modeling has been applied for predicting breast cancer outcomes, including risk of diagnosis, 22,23 prognosis, 24 treatment adherence, 25 and treatment morbidity. 26 In this present study, we sought to create an ML model to predict the probability of requiring PMRT after IBR. Secondarily, we aimed to compare the performance of ML to traditional regression methods for prediction modeling in this clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] During phase 2, the analytic phase (the statistical modeling and analysis of the data), many Analytic Real World Methods (ARWM) have been developed to analyze RWD, from the statistical, epidemiological, and computer-science communities. [19,[23][24][25] During phase 3, the post-analytic phase, sensitivity analyses establish the robustness of conclusions to reasonable uncertainty in assumptions. [24][25][26][27] In the current paper, we call the entire set of methods in these 3 phases of research "recommended Real World Methods (recommended RWM).…”
Section: Introductionmentioning
confidence: 99%